Trust and trustworthy computing : 7th International Conference, TRUST 2014, Heraklion, Crete, June 30 - July 2, 2014. Proceedings - Ioannidis, Sotiris; Holz, Thorsten (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Trust and Trustworthy Computing, TRUST 2014, held in Heraklion, Crete, Greece in June/July 2014. The 10 full papers and three short papers presented together with 9 poster abstracts were carefully reviewed and selected from 40 submissions. They are organized in topical sections such as TPM 2.0, trust in embedded and mobile systems; physical unclonable functions; trust in the web; trust and trustworthiness.